A culturally nuanced exploration of adolescent career decision-making and mental health challenges - Sunday Otu, Mkpoikanke; N. Onyishi, Charity (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2024)
Purpose - This study examines the complex relationship between career decision-making and mental health challenges among adolescents, with a focus on the sociocultural factors that influence their experiences. Method - A qualitative research design was employed, utilizing in-depth interviews and focus group discussions with adolescents aged 15 to 18. Secondary participants, including teachers, counsellors, and parents, provided additional perspectives. Results - The findings reveal that adolescents' career choices are shaped by parental expectations, peer influences, cultural norms, and gender roles. These factors contribute to increased stress, anxiety, and indecision. Urban adolescents reported feeling overwhelmed by societal expectations and the abundance of career options, whereas rural adolescents faced restricted opportunities and societal pressure to follow traditional career paths. Furthermore, inadequate access to career guidance and mental health support services exacerbated these challenges. Implications - The study highlights the necessity for culturally adapted interventions that integrate career counselling and mental health support. Such interventions can empower adolescents to make informed career decisions while addressing their emotional well-being. Originality/Value - This research provides constructive insights into the underexplored relationship between mental health and career decision-making within sociocultural contexts in Nigeria. It highlights the importance of addressing sociocultural dynamics to develop effective support systems for adolescents in diverse settings. *** Tujuan - Penelitian ini mengkaji hubungan kompleks antara pengambilan keputusan karier dan tantangan kesehatan mental di kalangan remaja, dengan fokus pada faktor sosiokultural yang memengaruhi pengalaman mereka. Metode - Desain penelitian kualitatif digunakan, dengan menggunakan wawancara mendalam dan diskusi kelompok terfokus dengan remaja berusia 15 hingga 18 tahun. Partisipan sekunder, termasuk guru, konselor, dan orang tua, memberikan perspektif tambahan. Hasil - Temuan menunjukkan bahwa pilihan karier remaja dibentuk oleh harapan orang tua, pengaruh teman sebaya, norma budaya, dan peran gender. Faktor-faktor ini berkontribusi pada peningkatan stres, kecemasan, dan keraguan. Remaja di perkotaan melaporkan bahwa mereka merasa terbebani oleh ekspektasi masyarakat dan banyaknya pilihan karier, sedangkan remaja di pedesaan menghadapi kesempatan yang terbatas dan tekanan masyarakat untuk mengikuti jalur karier tradisional. Selain itu, akses yang tidak memadai terhadap bimbingan karier dan layanan dukungan kesehatan mental memperparah tantangan-tantangan ini. Implikasi - Studi ini menyoroti perlunya intervensi yang disesuaikan dengan budaya yang mengintegrasikan konseling karier dan dukungan kesehatan mental. Intervensi semacam itu dapat memberdayakan remaja untuk membuat keputusan karier yang tepat sambil menangani kesejahteraan emosional mereka. Keaslian/Nilai - Penelitian ini memberikan wawasan konstruktif tentang hubungan yang belum dieksplorasi antara kesehatan mental dan pengambilan keputusan karier dalam konteks sosiokultural di Nigeria. Penelitian ini menyoroti pentingnya menangani dinamika sosiokultural untuk mengembangkan sistem dukungan yang efektif bagi remaja di lingkungan yang beragam.